The Caucasian relicts: a new species of the genus Niphargus (Crustacea: Amphipoda: Niphargidae) from the Gelendzhik–Tuapse area of the Russian southwestern Caucasus - Marin, Ivan; Krylenko, Sergey; Palatov, Dmitry (Zootaxa, 2021)
A new species of the genus Niphargus is described from the Gelendzhik–Tuapse area of the Russian southwestern Caucasus. It belongs to the “puteanus” species group and phylogenetically related to Caucasian N. ciscaucasicus and N. talikadzei, separating from other Caucasian species of the genus by the presence of 2 hooks in retinacules on pleopods, different rami of uropod I both in males and females, and relatively large inner ramus of uropod III. Molecular study has revealed that Niphargus bzhidik sp. nov. and related N. ciscaucasicus are relicts of the Late Miocene speciation, associated with the Messinian crisis (5.96–5.33Mya) separated widespread Paratethys species, which survived in long-term genetic isolation for a long time. The new species is blind and epigean, and probably unable to spread over long distances, but this way of life probably allowed surviving in refugee during the Quaternary period with a colder climate. Analysis of stable isotopes (δ13C/δ15N) revealed that the new species is carnivorous, in contrast to another studied stygobiotic herbivorous Niphargus species (e.g., Niphargus cf. tauricus). The key to the Caucasian and Eastern Asian species of the genus Niphargus, known from the territory of the former USSR, is presented in the article. [http://zoobank.org/urn:lsid:zoobank.org:act:E0019189-2432-4B64-B153-94C43FDD93E3]